Quality assessment of metals and alloys under high-speed loading - Куриляк, Валентина Василівна (Technology audit and production reserves, 2016)
The object of this research is analysis of parameters of metals and alloys under conditions of high-speed loading. One of the most problems in the research is the interaction between the impactor and the target, which is characterized simultaneously display of different effects, which determine the properties of the target and, in general, the impactor and the ratio of operating pressures and tensions that arise. So, some strength characteristics of steel grades are used as indicators of strength, because depending on the ratio of pressure and stress may highlight the areas of the most concrete demonstration of effects. The study found that the existing expert approach to assessing the quality parameters of materials under high-speed loading does not ensure the production of mathematically reliable data. This is due to the fact that the materials of steel origin under the influence of impactor react by increasing cleavage strength, while local warming up in the materials of metal group there is transition in fragile state with a shift in the area with higher specific impact energy. It is found that ferritic-pearlitic steel have a low cleavage strength and martensitic steel - high cleavage strength.